Running a journal club in 2020: reflections and challenges. (December 2021) - Mark, Isabel; Sonbol, Motaz; Abbasian, Cyrus
Summary: The online environment brings both challenges and opportunities. The skills learned in journal clubs remain highly relevant where the ability to critique rapidly generated information and apply evidence to patient care is vital. Creativity and flexibility are needed to ensure that learners' needs are met and efforts are made to involve those who may not be naturally drawn to online environments. This article explores how journal clubs have been approached in the past, both in person and more recently online, considers techniques for maintaining engagement in online teaching and proposes new approaches for future journal clubs.